2022
DOI: 10.3390/s22072504
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Ultrasonic Wave-Based Damage Detection of Railway Tracks Using PZT/FBG Hybrid Sensing System

Abstract: Damage detection of railway tracks is vital to ensure normal operation and safety of the rail transit system. Piezoelectric sensors, which are widely utilized to receive ultrasonic wave, may be disturbed in the railway system due to strong electromagnetic interference (EMI). In this work, a hybrid ultrasonic sensing system is proposed and validated by utilizing a lead-zirconate-titanate (PZT) actuator and a fiber Bragg grating (FBG) sensor to evaluate damage conditions of the railway tracks. The conventional u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Sun et al [ 172 ] presented a hybrid ultrasonic sensing system termed diffuse ultrasonic wave (DUW) to detect damage in railway tracks using a lead-zirconate-titanate (PZT) actuator and a fiber Bragg grating (FBG) hybrid sensing system. The experimental results revealed that the DUW signals recorded by the hybrid sensing system have a high potential for damage detection on railway tracks.…”
Section: Ndt Systemsmentioning
confidence: 99%
“…Sun et al [ 172 ] presented a hybrid ultrasonic sensing system termed diffuse ultrasonic wave (DUW) to detect damage in railway tracks using a lead-zirconate-titanate (PZT) actuator and a fiber Bragg grating (FBG) hybrid sensing system. The experimental results revealed that the DUW signals recorded by the hybrid sensing system have a high potential for damage detection on railway tracks.…”
Section: Ndt Systemsmentioning
confidence: 99%
“…As part of a local monitoring system, Sun et al. [ 119 ] presented a hybrid ultrasonic sensing system, named diffuse ultrasonic wave (DUW), to detect damage to railway tracks using a lead–zirconate–titanate (PZT) actuator and an FBG hybrid sensing system. The experimental results showed that DUW signals could detect damage on railway tracks more effectively than the energy-based index.…”
Section: Structural Health Monitoringmentioning
confidence: 99%
“…It has been proved that the scattered waves contained the rich information about the damage. 24,25 The time differences of the damage induced scattered waves are contained in the sidebands, which could be utilized for damage localization. 2628 It is interesting to cooperate the elliptical trajectory location method (ETLM) with the time differences obtained from the time reversal method to achieve baseline-free damage localization.…”
Section: Introductionmentioning
confidence: 99%